Prevalence of Syphilis among People living with HIV (PLHIV) attending a tertiary care hospital in coastal south India - Madi, Deepak; Achappa, Basavaprabhu; Vernakar, Poonam; Bhaskaran, Unnikrishnan; Ramapuram, John T; Mahalingam, Soundarya (Asian Journal of Medical Sciences, 2015)
Background: Syphilis and HIV are both transmitted sexually so people can be infected with both diseases. Co-infection of syphilis and HIV alters the course of both the diseases. Venereal disease research laboratory (VDRL) test is a non-treponemal test, used commonly in Antiretroviral Therapy Centres (ART) in India to detect syphilis. The aim of our study was to determine the prevalence of syphilis in HIV-infected patients attending a tertiary care hospital using VDRL test. Materials and Methods: Using a cross-sectional study design 113 HIV positive patients were included. VDRL test was used to screen for syphilis. The collected data was analyzed using SPSS version 11.5. Results: Among the 113 patients screened 69(61%) were males and 44(39%) were females. Majority of the patients had acquired the disease through heterosexual transmission (92.9%). VDRL test was negative in all 113 patients. Conclusion: The seroprevalence of syphilis in coastal South India using VDRL is very less. Specific tests like Fluorescent Treponemal Antibody Absorption test (FTA-ABS) or Treponema pallidum hemagglutination Assay (TPHA) would be beneficial to detect asymptomatic syphilis in ART centers. DOI: http://dx.doi.org/10.3126/ajms.v6i6.11623 Asian Journal of Medical Sciences Vol.6(6) 2015 77-79